2009
DOI: 10.1016/j.bmcl.2009.10.081
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumoral activity of imidazoquines, a new class of antimalarials derived from primaquine

Abstract: a b s t r a c tThe growth inhibitory activity of imidazoquines, antimalarial imidazolidin-4-ones derived from primaquine, on human cancer cell lines HT-29, Caco-2, and MCF-7 has been evaluated. Primaquine, N-dipeptidyl-primaquine derivatives, and other quinolines have been included in the study for comparison purposes. Primaquine and some of its derivatives were significantly active against the MCF-7 human breast cancer cell line, so these compounds might represent useful leads targeted at the development of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This phenomenon was already noted in the authors' previous work with urea derivatives of PQ 20 . Some other authors reported selectivity of quinidine, PQ, N-dipeptidylprimaquines and imidazolin-4-one PQ derivatives towards MCF-7 cell line as well 16,29 . Selective growth inhibitory activity towards breast cancer cells could be explained by selective induction of cytochrome P450 (CYP-1) enzymes specifically in the MCF-7 line, known as CYP-1 inducible cell line 30 .…”
Section: Cytostatic Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…This phenomenon was already noted in the authors' previous work with urea derivatives of PQ 20 . Some other authors reported selectivity of quinidine, PQ, N-dipeptidylprimaquines and imidazolin-4-one PQ derivatives towards MCF-7 cell line as well 16,29 . Selective growth inhibitory activity towards breast cancer cells could be explained by selective induction of cytochrome P450 (CYP-1) enzymes specifically in the MCF-7 line, known as CYP-1 inducible cell line 30 .…”
Section: Cytostatic Activitymentioning
confidence: 96%
“…Mahajan et aldescribed 7-chloroquinolyl thioureas as potential antimalarial and anticancer agents 15 . Several research groups found dual antimalarial and anticancer activity of both quinoline and trioxane derivatives as well [16][17][18] . Based on these findings, we have synthesized a series of compounds containing the antimalarial drug primaquine (PQ) substituted by an N-4-cycloalkyl, aryl,…”
Section: Introductionmentioning
confidence: 99%
“…The present study provided proof-of-concept regarding the expected high enzymatic stability of primaquine-derived imidazolidin-4-ones, imidazoquines (9), formerly developed in our group as potential alternatives to the parent antimalarial with improved oral bioavailability [29][30][31][32][33][53][54][55]. Relevant experimental evidence on the remarkably low propensity of imidazoquines to undergo metabolic conversions, mediated by rat liver enzymes, was obtained.…”
Section: Discussionmentioning
confidence: 69%
“…All compounds were active in vitro on P.berghei-infected hepatocytes and most of them were also active against P. carinii [32]. To test these hypotheses, we have profiled, by means of mass spectrometry techniques, the metabolic behaviour of PQ and one of its most active and "drug-like" derivatives, 9.2 [32,33], in combined rat liver cytosolic and microsomal protein fractions. This suggests that they will probably have a significantly higher oral bioavailability than PQ, which would allow usage of lower doses and, hence, lead to decreased levels of toxic PQ-derived metabolites [32].…”
Section: Introductionmentioning
confidence: 99%
“…We found that COLresistant KBV20C cells can be sensitized at COL concentrations 4-fold higher than that required for parent sensitive KB cells, suggesting that P-gp activity is saturated at high COL concentrations. The cancer-sensitizing ability of anti-malarial drugs has been demonstrated in various cancer models (13)(14)(15)(16)(17), suggesting that anti-malarial drugs have potential as chemotherapeutic agents. CHL, MEF and PRI treatment may increase the toxicity of other chemotherapeutics through their P-gp inhibitory activity (18,19), which increases their clinical potential.…”
Section: Discussionmentioning
confidence: 99%